2021
DOI: 10.3389/fcell.2021.788955
|View full text |Cite
|
Sign up to set email alerts
|

Insights to Heart Development and Cardiac Disease Models Using Pluripotent Stem Cell Derived 3D Organoids

Abstract: Medical research in the recent years has achieved significant progress due to the increasing prominence of organoid technology. Various developed tissue organoids bridge the limitations of conventional 2D cell culture and animal models by recapitulating in vivo cellular complexity. Current 3D cardiac organoid cultures have shown their utility in modelling key developmental hallmarks of heart organogenesis, but the complexity of the organ demands a more versatile model that can investigate more fundamental para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 108 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…At present, there are other platforms that can assess parameters such as chamber wall thickening, ejection fraction and pressure generation [50][51][52]. Each of these alternative platforms suffer from their own set of drawbacks, but are primarily limited by the lack of self-organization and incomparability with actual human [53]. While existing 2D models demonstrate capabilities of measuring contraction rhythm and calcium transient dynamics in vitro, CCOs provide a platform to maintain and mature the various cardiovascular sub-types in 3D, mimicking the function of an in vivo heart and provided important output parameters such as heart wall thickness, fractional shortening, simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are other platforms that can assess parameters such as chamber wall thickening, ejection fraction and pressure generation [50][51][52]. Each of these alternative platforms suffer from their own set of drawbacks, but are primarily limited by the lack of self-organization and incomparability with actual human [53]. While existing 2D models demonstrate capabilities of measuring contraction rhythm and calcium transient dynamics in vitro, CCOs provide a platform to maintain and mature the various cardiovascular sub-types in 3D, mimicking the function of an in vivo heart and provided important output parameters such as heart wall thickness, fractional shortening, simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Wang et al prepared Pyridine-grafted diblock copolymer poly(caprolactone- graft -pyridine)-block-poly(caprolactone) [P(CL- g -Py)- b -PCL] by combining ring-opening polymerization and Cu(I) catalyzed azide-alkyne cycloaddition (CuAAC) reaction [ 146 , 147 ]. They were able to create core-shell nanoparticles (CSNPs) by self-assembling transferrin (Tf) and P(CL- g -Py)- b -PCL, where the PCL block helped to encapsulate DOX (with a 10% loading capacity) through hydrophobic-hydrophobic interaction [ 148 , 149 , 150 ]. The drug-loaded Tf/P(CL- g -Py)- b -PCL CSNPs exhibited effective targeting of MCF-7 cancer cells by binding to transferrin receptors (TfR) through Tf [ 147 ].…”
Section: Strategies To Target Pcl-based Drug Delivery Carriersmentioning
confidence: 99%
“…With an enhanced mechanistic insight into how the virus induces cardiac damage, it was further shown that bromodomain and extraterminal family inhibitors (BETi) could ameliorate cardiac dysfunction in the organoids while decreasing viral responses transcriptionally and decreasing the infection rate of cardiomyocytes by SARS-CoV-2 [ 75 ]. With emerging infectious diseases, cardiac organoids could also be valuable in studying myocarditis due to infection by viruses and protozoa such as Trypanosoma cruzi ( T. cruzi ) [ 127 , 128 ]. T. cruzi infection results in Chagas disease, which is the leading cause of myocarditis [ 129 ].…”
Section: Common Infectious Diseases Modelled By Organoidsmentioning
confidence: 99%